Aspirations for Higher Education among Newcomer Refugee Youth in Toronto: Expectations, Challenges, and Strategies - Shakya, Yogendra B.; Guruge, Sepali; Hynie, Michaela; Akbari, Arzo; Malik, Mohamed; Htoo, Sheila; Khogali, Azza; Mona, Stella Abiyo; Murtaza, Rabea; Alley, Sarah (Refuge: Canada’s Journal on Refugees, 2012)
A large percentage of refugees have low levels of education and official language fluency upon arrival in Canada. Thi spaper discusses educational goals of newcomer refugee youth from three communities in Toronto (Afghan, Karen, and Sudanese), and explores how these are linked to premigration and post-migration determinants. Guided by community-based research principles, we collaborated with eight refugee youth peer researchers and conducted ten focus groups and thirteen interviews with refugee youth. Results show that newcomer refugee youth develop strong aspirations for higher education in Canada as a proactive response to overcome pre-migration experiences of forced migration and educational disruptions. We then discuss how these youth negotiate educational goals in post-migration context in relation to shifts in family responsibilities and everyday encounter with multiple systemic barriers in Canada. In doing this, we examine the thin line between vulnerability and empowerment that refugee youth straddle and reveal policy gaps and contradictions in the depoliticized humanitarianism within refugee resettlement in Canada.